Business Intelligence for Educational Institution : A Literature Review - Maulida Hindrayani, Kartika (International Journal of Computer, Network Security and Information System, 2020)
Educational institution is one of the organizations that should manage data to improve decision making. Students, department, research, and community services, are the data that should be managed in education. Those data could help in accreditation, marketing, and operational process. Business Intelligence (BI) helps visualize a huge amount of data. Executives will easily understand what the data try to imply in graphics. In this research, literature review about BI in educational organization will be conducted.